2017
DOI: 10.14429/djlit.37.3.10918
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Web 2.0 Applications in Academic Libraries in India

Abstract: The adoption of Web 2.0 tools in academic libraries in India, the barriers and motivating factor to its use is investigated. The study involved an exploratory survey of the contents of the academic library websites in India. The websites of 28 Central Universities, 16 Indian Institutes of Technology (IITs) and 13 Indian Institutes of Management (IIMs) were identified for the study. A structured questionnaire was mailed to library professionals from selected Universities and Institutes in India. The findings su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…These findings were similar to a study conducted by Santosh (2017), where the findings revealed that majority of the information professionals were familiar with Facebook (86.25%), Wikipedia (85%), YouTube (80%), and Blogs (79%). In a study conducted by Okello-Obura and Ssekitto (2015) in Africa, it was reported that the majority of educators were familiar and comfortable with the use Web 2.0 tools, which augured well for their usage in education.…”
Section: Familiarity With Web 20 Toolssupporting
confidence: 89%
“…These findings were similar to a study conducted by Santosh (2017), where the findings revealed that majority of the information professionals were familiar with Facebook (86.25%), Wikipedia (85%), YouTube (80%), and Blogs (79%). In a study conducted by Okello-Obura and Ssekitto (2015) in Africa, it was reported that the majority of educators were familiar and comfortable with the use Web 2.0 tools, which augured well for their usage in education.…”
Section: Familiarity With Web 20 Toolssupporting
confidence: 89%
“…To provide research support to the scholarly community of its parent institute, a library adopts various online tools and guides the researchers to use those tools at different stages of their research pursuit. The rapid development of online technologies has encouraged libraries to switch over to innovative and quicker access to resources and facilities (Garoufallou and Charitopoulou, 2012;Mahmood and Richardson, 2013;Santosh, 2017). Research services of a library encompass offering various research tools and techniques to provide thorough support to research activities.…”
Section: Introductionmentioning
confidence: 99%